Imaging of Urinary Tract Diverticula - Builov, Vladimir M. (Springer International Publishing : Imprint: Springer, 2014)
This monograph covers all aspects of the radiologic diagnosis of urinary tract diverticula, including calyceal, ureteral, bladder, and urethral diverticula. Characteristic and subtle diagnostic features are identified with the aid of numerous high-quality ultrasound, X-ray, and magnetic resonance images, the vast majority of which are drawn from the author’s personal clinical practice. In addition, issues relating to terminology, classification, statistics, etiology, pathogenesis, clinical presentation, and differential diagnosis are discussed. The text is complemented by two helpful appendices that document the latest recommendations of the European Society of Urogenital Radiology regarding use of contrast media and the European Medicines Agency on minimizing the risk of nephrogenic systemic fibrosis when using gadolinium-containing contrast agents. This book will be of value for specialists in radiology and urology and also trainees and medical students.  .